Manual Descriptivo de Clases y Puestos del Centro de Estudios y Capacitación Cooperativa CENECOOP R.L. y la Universidad FUNDEPOS - Monterrosa-Madriz, Lashmi (Instituto Tecnológico de Costa Rica., 2021)
This project allows to demonstrate how a descriptive manual of classes and positions can help a company to implement its strategy through the clarification of the roles and responsibilities to the people who compose it. In the search for continuous improvement, the integration of this tool in a company facilitates the development of human talent management activities, it also serves as a foundation for the development of other processes for the improvement of the capital human and consequently of the productivity of the company. This project was developed under a qualitative and descriptive approach where an action-research design was used to collect the information through the application of a questionnaire, to finally be able to assemble a proposal for the descriptive manual of classes and positions of CENECOOP R.L and the FUNDEPOS University, which contribute to the achievement of the organizational strategy of each of these companies.

Este proyecto permite demostrar cómo un manual descriptivo de clases y puestos puede ayudar a una empresa a implementar su estrategia a través de la clarificación de los roles y responsabilidades de las personas que la componen. En la búsqueda del mejoramiento continuo, la integración de esta herramienta en una empresa facilita el desarrollo de las actividades de la gestión del talento humano, además sirve como base para el desarrollo de otros procesos de mejora del capital humano y por consiguiente de la productividad de la empresa. Este proyecto se desarrolló bajo un enfoque cualitativo y descriptivo en donde se empleó un diseño de investigación-acción para la recolección de la información a través de la aplicación de un cuestionario para finalmente poder montar una propuesta del manual descriptivo de clases y puestos del CENECOOP R.L y la Universidad FUNDEPOS, el cual, contribuye al logro de la estrategia organizacional de cada una de estas empresas.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas. 2021.
Keywords: Centro de Estudios y Capacitación Cooperativa CENECOOP R.L.; Universidad FUNDEPOS; Costa Rica; Manuales de puestos; Manuales descriptivos; Administración de empresas; Career Handbook; Management - Handbooks, manuals, etc.; Business enterprises - Management